Complex supramolecular tessellations with on-surface self-synthesized C60 tiles through van der Waals interaction. Issue 4 (11th January 2022) - Zhang, Xin; Ding, Haoxuan; Chen, Xiaorui; Lin, Haiping; Li, Qing; Gao, Jianzhi; Pan, Minghu; Guo, Quanmin
Abstract : Simultaneous on-site synthesis of C60 -based hexagonal and rectangular tiles and self-organized tiling through van der Waals interaction. Abstract : Supramolecular tessellation with self-synthesized (C60 )7 tiles is achieved based on a cooperative interaction between co-adsorbed C60 and octanethiol (OT) molecules. Tile synthesis and tiling take place simultaneously on a gold substrate leading to a two-dimensional lattice of (C60 )7 tiles with OT as the binder molecule filling the gaps between the tiles. This supramolecular tessellation is featured with simultaneous on-site synthesis of tiles and self-organized tiling. In the absence of specific functional groups, the key to ordered tiling for the C60 /OT system is the collective van der Waals (vdW) interaction among a large number of molecules. This bicomponent system herein offers a way for the artificial synthesis of 2D complex vdW supramolecular tessellations.